OPTIMIZATION OF IMPLEMENTATION OF SYSTEM IRRIGATION FOR IMPROVING AGRICULTURAL RESULTS IN CEPU-BLORA - Hariyanto Hariyanto (Reviews in Civil Engineering, 2018)
The results showed that 9 (nine) villages implemented technical irrigation by utilizing underground water as irrigation network in each plot of farmer land there was one village applying an irrigation network of open tapping channel from the river.The results showed that there were 8 (eight) villages with rain-fed irrigation system. Farmers harvested in Cepu from 17 villages on average of 2.35 tons in 2015 and 2.33 in 2016 average land area of 0.5 ha. Types of irrigation networks covered by 0.42 m3 / min average water discharge able to win the average land of 0.5 ha for 40 hours (two days) of water flowing into rice fields, planting pattern with SRI method applying 2/10 to achieve optimal and efficient results water usage